Analysis of physical layer performance of data center with optical wavelength switches based on advanced modulation formats. Issue 3 (4th May 2018) - Ahmad, Iftikhar; Chughtai, Mohsan Niaz
ABSTRACT: In this paper the IRIS (Integrated Router Interconnected spectrally), an optical domain architecture for datacenter network is analyzed. The IRIS integrated with advanced modulation formats (M-QAM) and coherent optical receiver is analyzed. The channel impairments are compensated using the DSP algorithms following the coherent receiver. The proposed scheme allows N2 multiplexed wavelengths for N×N size. The performance of the N×N-IRIS switch with and without wavelength conversion is analyzed for different Baud rates over M-QAM modulation formats. The performance of the system is analyzed in terms of bit error rate (BER) vs OSNR curves.